Novos mecanismos de coordenação no mercado do trigo brasileiro no período de 1990/2005. - Perosa, Bruno Benzaquen (Universidade Federal de São Carlos, 2007)
The wheat chain, as most of Brazilians agri-food chains, has had deep changes on the institutional environment since 1990, when the Brazilian economy was open and most of the industry sectors were deregulated (the State diminished the regulation). The effects of those changes were amplified by the MERCOSUR agreement. As a consequence, a complete change of the ways coordination on the Brazilian wheat market takes place was noticed. The relations between wheat producers and milling units, which before 1990 was intermediated by State agencies like Banco do Brasil and DTRIG, where totally transferred to the private sector. The cooperative system and the representative associations, which used to focus on the political representation, had to adapt their work and offer different services for their members. The analysis of the new forms of relationships on this market after 1990 shows that the regulatory framework which shaped the activities of the sector for many decades had a strong influence on the new dynamics of coordination after the State reduced the intervention. This study aims to analyze how the Brazilian wheat market was regulated before and after 1990, highlighting the impact of institutional environment at different times on the dynamics of the relationships and coordination among those actors playing on the market after 1990. With this goal, this study will refer to theoretical approaches linked to the neo-institutionalism, as the Transaction Cost and Measurement Economics, the Network Analysis, and the Policy Networks. These references will support the preparation of indicators to explore the vertical coordination (among actors of different tiers) and horizontal coordination (among actors of the same tier).
Keywords: Agribusiness; Trigo; Ambiente institucional; Cadeias agroindustriais coordenação; Wheat; Institutional environment; Coordination; ENGENHARIAS::ENGENHARIA DE PRODUCAO